Taxonomic notes and description of the male of Xenochlora nigrofemorata (Smith, 1879) (Hymenoptera: Apidae: Halictinae) - Santos, Leandro M.; Melo, Gabriel A.r. (Zootaxa, 2013)
The present work describes for the first time the male of the bee genus Xenochlora Engel, Brooks & Yanega, 1997. The male of X. nigrofemorata (Smith, 1879) is described and illustrated. Additionally, Megalopta opacicollis Friese, 1926 is placed as a junior synonym of X. nigrofemorata (Smith, 1879).